On the influence of water conductivity, pH and climate on bryophyte assemblages in Catalan semi-natural springs. (3rd April 2018) - Bes, M.; Corbera, J.; Sayol, F.; Bagaria, G.; Jover, M.; Preece, C.; Viza, A.; Sabater, F.; Fernández-Martínez, M.
Abstract : Bryophytes are some of the most sensitive biological indicators of environmental change. Springs have a significant presence of bryophytes and so are ideal habitats for studying their relationship with the environment. We tested whether bryophyte assemblages can be explained with macro-, meso- and micro-ecological variables (i.e. seasonal climate, altitude, water pH and conductivity) sampling bryophytes from 198 semi-natural springs distributed along montane regions in the north-eastern Iberian Peninsula. We tested the influence of environmental variables on bryophyte assemblages in springs using sparse Partial Least Squares. Our results show that variability in bryophyte assemblages is explained by seasonal climate (temperature and precipitation from winter, spring, summer and autumn and temperature and precipitation seasonality), altitude and water conductivity. The results obtained by the present study will be useful for predicting bryophyte diversity in springs using simple and easy to obtain variables such as climate, water pH and conductivity.